Whole-Genome Sequencing Analysis Revealed High Genomic Variability, Recombination Events and Mobile Genetic Elements in Streptococcus uberis Strains Isolated from Bovine Mastitis in Colombian Dairy Herds - Paola A. Rios Agudelo; Julián Reyes Vélez; Martha Olivera Angel; Adam M. Blanchard; Yesid Cuesta Astroz; Arley Caraballo Guzmán; Giovanny Torres Lindarte (Antibiotics)
Introduction: Streptococcus uberis is a poorly controlled cause of bovine intramammary infections and a common motivation for the use antibiotics in dairy farms worldwide. Therefore, studying the genomic characteristics of this pathogen is fundamental to understand its complex epidemiology and behavior against antimicrobials. Methods: A comparative genomic analysis of 10 S. uberis strains was performed and their antimicrobial susceptibility was assessed. Results: Ten different novel sequence types were found, and genes (tetM, tetO, patB, lnuC, lnuA, lsaE, ermB, ANT(6)-la) and mobile genetic elements previously associated with antimicrobial resistance (repUS43, ISSag2, and ISEnfa4) and virulence (315.2 phage) were detected. Additionally, our strains had the highest relative rate of recombination to mutation (8.3) compared to other S. uberis strains isolated from different continents (America: 7.7, Asia: 2.9, Europe: 5.4, and Oceania: 6.6). Most of the strains (80%) tested showed phenotypic resistance to clindamycin and 70% exhibited intermediate susceptibility to penicillin. Conclusions: The high heterogeneity of strains observed and the presence of genetic factors linked to antimicrobial resistance represent a challenge for the implementation and surveillance of measures focused on the control and elimination of this pathogen.